ANALISIS KESULITAN GURU KELAS RENDAH SDN 18 SENAIN MENGAJAR TEMATIK DI MASA PANDEMI COVID-19 - Siti Jumaida; Mastiah Mastiah; Muhammad Akip (Bestari: Jurnal Pendidikan dan Kebudayaan, 2022)
Abstract: The purpose of this research was to find out what are the difficulties and how to solve the problems of low grade teachers at SDN 18 Senain in Thematic learning during the Covid-19 Pandemic. This study used a descriptive qualitative research method that carried out an in-depth analysis of the difficulties and solutions to overcome the problems of low grade teachers at SDN 18 Senain in Thematic learning during the Covid-1 Pandemic. The instruments used to collect data were questionnaire sheets, interviews and documentation. From the results of the analysis, it was found that the thematic learning process for low-grade students at 18 Senain Elementary Schools during the Covid-19 pandemic The problems experienced by teachers in the implementation of offline classes (outside the network) during the covid-19 pandemic period in thematic learning of low-grade students in schools The basics of Negeri 18 Senain are limited facilities and knowledge regarding offline methods, limited face-to-face time, lack of parental assistance during learning, causing students to lack discipline, student complaints about piling up tasks and a lack of supporting books for both teachers and students. Efforts to overcome teacher problems in the implementation of offline classes during the Covid-19 pandemic in the thematic learning of low-grade students at 18 Senain Elementary School, namely by coordinating with parents about the willingness to accompany children when working on assignments at home, teachers Once upon a time you can go to the student's house to provide teaching materials to students or contact the parents directly to give assignments, provide large grants from BOS for visiting teacher PJJ activities, teachers reduce assignments so that students don't feel overwhelmed ..Keywords: Analysis, Covid-19 Pandemic, Thematic and Offline Learning. Abstrak: Tujuan diadakan penelitian ini adalah untuk mengetahui apa saja kesulitan dan bagaimana solusi mengatasi permasalahan guru kelas rendah SDN 18 Senain dalam pembelajaran Tematik di Masa Pandemi Covid-19. Penelitian ini menggunakan metode penelitian kualitatif deskriptif yang melakukan analisis secara mendalam tentang kesulitan dan bagaimana solusi mengatasi permasalahan guru kelas rendah SDN 18 Senain dalam pembelajaran Tematik di Masa Pandemi Covid-1. Instrumen yang digunakan untuk mengumpulkan data adalah lembar angket, wawancara dan dokumentasi.Dari hasil analisis didapatkan bahwa Proses pembelajaran tematik pada siswa kelas rendah di Sekolah Dasar Negeri 18 Senain selama masa pandemi covid-19 Problematika yang dialami guru dalam pelaksanaan kelas luring (luar jaringan) selama masa pandemi covid-19 pada pembelajaran tematik siswa kelas rendah di Sekolah Dasar Negeri 18 Senain adalah keterbatasan fasilitas dan pengetahuan mengenai metode luring, terbatasnya waktu tatap muka, kurangnya dampingan orang tua pada saat pembelajaran menyebabkan siswa kurang disiplin, keluhan siswa mengenai tugas yang sangat menumpuk dan kurangnya buku peunjang baik untuk guru maupun siswa. Upaya untuk mengatasi problematika guru dalam pelaksanaan kelas luring (luar jaringan) selama masa pandemi covid-19 pada pembelajaran tematik siswa kelas rendah di Sekolah Dasar Negeri 18 Senain yaitu dengan koordinasi bersama orang tua tentang kesediaan untuk mendampingi anak pada saat pengerjaan tugas di rumah, guru sekali waktu bisa mendatangi rumah siswa untuk memberikan materi ajar kepada siswa atau menghubungi langsung orang tua siswa untuk memberikan tugas, memberikan dana bantuan yang besasal dari BOS untuk kegiatan PJJ guru kunjung, guru mengurangi pemberian tugas agar siswa tidak merasa terbebani.. Kata Kunci: Analisis, Pandemi Covid-19, Tematik dan Pembelajaran Luring.